Plausible Scenarios for Thai Energy Businesses in the Next 30 Years - Nakapreecha, N.; Pongthanaisawan, J.; Wangjiraniran, W. (Frontiers in Energy Research, 2021)
Energy sector is currently facing different facets of challenges. It is necessary for the business leaders to understand what and how changes will affect their businesses in order to prepare themselves for the uncertainties and take advantage of new opportunities. This paper identifies changes that are expected to have impacts on Thailand’s energy system in the next 30 years and explores plausible scenarios of Thailand’s energy business under such changes. The study starts with an examination of global and local circumstances, from which a focal issue of the energy business is defined as “to achieve the sustainable development goals (SDG) by 2050”. Then, the STEEP analysis and consultations with stakeholders are implemented to identify business drivers and critical uncertainties, respectively. Policy and technology are found to be two of the most powerful factors affecting energy business and are, therefore, used as fundamental framework for scenario development. Accordingly, four plausible scenarios are derived providing different possible prospects of Thailand’s energy business. The findings can further be used in the analysis of national energy balance with detailed sector-by-sector projections. All of which will be beneficial in the strategic energy planning at both national and corporate level with a view to achieving the SDGs by 2050.